A study of Industry 4.0 technologies and customer perception in the insurance industry - Busschau, Mary C.B (My University, 2021)
The changes in society and business towards a more digitised and connected world evoke feelings of both excitement and anxiety. Businesses are increasingly using these technologies to ensure optimal customer service and delivery of services and products, but the literature shows that many customers may not be ready for this change. Industry 4.0 technologies such as big data, artificial intelligence, and the internet of things are bringing increased awareness around customer concerns on privacy, fear of autonomous robots and artificial intelligence, and a general distrust of new technology. This research study looks at the potential issues that customers have with digital technology and their perceptions of South African insurance providers using this technology. The research also looks at whether customer education and communication have an impact on these areas of privacy concerns, fear of autonomous robots and artificial intelligence and distrust of new technology and customer perception. A quantitative research method was applied through an online survey, of which 395 participants formed the segment. Using correlation statistics and structural equation modelling the results showed that a unit increase in privacy concerns was more likely to improve their perceptions towards insurance by as much as 17.9%. The results also suggest that there is a 26% chance that improvements in trust in technologies could positively impact respondents' perceptions of insurance. The study also revealed that fear of autonomous robots and artificial intelligence have nothing to do with customer perceptions; results were not significant at the 5% level. Further results indicated that customer education and transparent communication significantly impact customer perception related to privacy concerns by 61.15% and distrust of new technologies by 143.15%. These results support most of the theories from the literature
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Industry 4.0; Customer perception; Internet of Things; UCTD